From Lab to Shelf: Gelatin-Based pH Sensors Revolutionizing Food Packaging - Ruirui Wang (Gels)
The development of multifunctional smart food packaging has garnered considerable attention in research. Gelatin exhibits outstanding characteristics, featuring remarkable gel strength, molecular binding affinity, excellent colloidal dispersibility, low solution viscosity, sustained dispersion stability, and significant water retention properties. Gelatin-based film is ideally suited for the developing simple, portable, and rapid pH sensors, owing to its satisfactory biocompatibility, biodegradability, biosafety, affordability, and facilitation of easy handling and usage. This paper aims to explore the challenges and opportunities relating to gelatin-based pH sensors. It begins by outlining the sources, classifications, and functional properties of gelatin, followed by an analysis of the current research landscape and future trends related to intelligent indicators and active carriers. Subsequently, potential research directions for gelatin-based pH sensors are proposed. Using a literature analysis, it can be concluded that novel gelatin-based smart packaging represents the future of food packaging. It is hoped that the paper can provide some basic information for the development and application of gelatin-based smart packaging.